Creb5 controls its own expression and directly induces the joint interzone regulatory program - Cheng-Hai Zhang; Aref Shahini; Laura E. Cook; Meeta Mistry; Jongkil Kim; Heather Wick; Len A. Pennacchio; Andrew B. Lassar (Proceedings of the National Academy of Sciences, 2025)
Prior studies have indicated that the transcription factor Creb5 is expressed in the joint interzone, which contains the progenitors for all synovial joint tissues in both mouse and human embryos. In the absence of Creb5 function, most synovial joint interzones fail to form and the cartilage templates in the long bones remain fused. This earlier work did not clarify whether Creb5 initiates a cascade of signaling molecules, such as growth and differentiation factor 5 (Gdf5) and Wnt-family members, that in turn induce the formation of the joint interzone, or instead directly activates the expression of joint interzone markers. In the present study, an integrative analysis of the transcriptome, chromatin accessibility, and Creb5-occupancy in joint progenitors revealed that Creb5 directly binds to both its own two promoters and to the regulatory regions of Gdf5 and Sfrp2 , each of whose expression in the joint interzone is Creb5-dependent. Functional enhancer analysis indicated that Creb5 binding sites in either the two Creb5 promoters, or in Gdf5 and Sfrp2 regulatory elements are necessary for these sequences to drive transgene expression in the developing synovial joints. While Creb5 directly drives Gdf5 and Sfrp2 expression in the inner joint interzone, Creb5 activates Barx1 expression specifically in the outer joint interzone. Our findings indicate that Creb5 initiates a regulatory network that both promotes the formation of synovial joints, and subsequently activates distinct transcriptional targets in the inner versus the outer regions of the joint interzone, thus regionalizing gene expression in the developing joint.